2020
DOI: 10.1111/tmi.13512
|View full text |Cite
|
Sign up to set email alerts
|

Insights in the pathophysiology of haemorrhagic strokes in a sub‐Sahara African country, an epidemiological and MRI study

Abstract: Objective Intra‐cerebral Haemorrhage (ICH) seems more prevalent in sub‐Saharan Africa (SSA) than in High‐Income Countries (HIC) with poorer clinical outcome. Higher impact of hypertension and/or amyloid angiopathy could account for this disproportion. Here, we sought to (i) retrospectively compare ICH clinical and imaging patterns in Belgium and Guinea and in a subsequent cohort (ii) prospectively compare brain MRI characteristics to seek evidence for a different proportion of amyloid angiopathy patterns. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 59 publications
(120 reference statements)
0
2
0
Order By: Relevance
“…Inhibition of PI3Kγ has been proposed as a macrophage-based cancer treatment strategy ( 27 ). Additionally, changes in AKT isoforms or AKT activity levels in macrophages determine the viability of monocytes/macrophages ( 28 , 29 ). The present study showed that overexpression of AKT in EC cells abolished the effect of overexpression of IGFBP-rP1 on M2 polarization, indicating that this regulation was dependent on the PI3K/AKT pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of PI3Kγ has been proposed as a macrophage-based cancer treatment strategy ( 27 ). Additionally, changes in AKT isoforms or AKT activity levels in macrophages determine the viability of monocytes/macrophages ( 28 , 29 ). The present study showed that overexpression of AKT in EC cells abolished the effect of overexpression of IGFBP-rP1 on M2 polarization, indicating that this regulation was dependent on the PI3K/AKT pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Hemorrhagic stroke can be classified as intracerebral hemorrhage or subarachnoid hemorrhage based on the site of the hemorrhage. With regard to ischemic stroke, a blood vessel is blocked, leading to sudden loss of blood flow, local cerebral ischemia, and cell death [9,10]. The global prevalence of ischemic stroke is twice as high as that of stroke [11]; however, ischemic stroke accounts for about 85% of all strokes in high-income countries [12].…”
mentioning
confidence: 99%